Human Papilloma Virus Associated Squamous Cell Carcinoma of the Head and Neck. (21st September 2015) - Ajila, Vidya; Shetty, Harish; Babu, Subhas; Shetty, Veena; Hegde, Shruthi
Abstract : Oral cancer is one of the commonest causes for mortality and morbidity with squamous cell carcinoma being the sixth most frequent malignant tumour worldwide. In addition to tobacco and alcohol, human papilloma virus (HPV) is associated with a proportion of head and neck cancers. As in cervical cancers, HPV types 16 and 18 are the cause of malignant transformation. HPV-positive cancers of head and neck have unique characteristics such as occurrence in a younger age group, distinct clinical and molecular features, and better prognosis as compared to HPV-negative carcinomas. They also possess the potential for prevention by using vaccination. The present review describes in detail the salient features of HPV associated oral squamous cell carcinoma (OSCC), its differences from HPV-negative OSCC, diagnostic features, and recent strategies in prevention and management.